Ugland, T. 2011, Jean Monnet and Canada: early travels and the idea of European unity. Toronto, Buffalo, and London: University of Toronto Press. - Pūras, Adomas (Baltic Journal of Political Science, 2015)
What does the European polity of twenty-eight member states owe to an eighteen-year-old Frenchman’s journey across Canada in 1907? This question preoccupies Trygve Ugland in his 2011 study Jean Monnet and Canada: early travels and the idea of European unity. Ugland presupposes there would hardly be a European Union to speak of if it weren’t for Jean Monnet; and he wonders whether there would be a Jean Monnet worth talking about if it weren’t for Monnet’s formative experiences in Canada as a salesman for his father’s cognac firm. [...]